The Antequera megalithic site in the work of Georg and Vera Leisner: a review - García Sanjuán, Leonardo; Mora Molina, Coronada; Bartelheim, Martin (SPAL - Revista de Prehistoria y Arqueología, 2019)
The Antequera dolmens site (Malaga, Spain), included in the UNESCO World Heritage List since July 2016, has a research history of almost 200 years that goes back to the work of Rafael Mitjana y Ardison in 1840s. After the discovery of the dolmen of Viera and the tholos of El Romeral, in 1903 and 1904 respectively, the research of the great megalithic site received a renewed impulse, both nationally and internationally. Published in 1943, the first volume of the great corpus of Iberian megalithic monuments by Georg and Vera Leisner (Die Megalithgräber der Iberischen Halbinsel, Erster Teil: Der Süden) was to become the most detailed and detailed study of the Antequera site during the second half of the 20th century, despite the fact that because it was published in German limited its penetration among Spanish scholarship. In this article we review the importance of the work of the Leisners to understand the characteristics of the Antequera megaliths in light of the results of the research that has been undertaken in the last 15 years. Many of the issues raised by the German couple continue to be fully pertinent within the context of today’s research on these monuments. In addition, to facilitate future access to their work, this paper is accompanied by full translations into English and Spanish of the Leisners’s work on the Antequera megaliths.